Do Individual Characteristics and Financial Burden Contribute to Health Problems? Evidence from Malaysia - Md Kassim, Aza Azlina; Rosli, Mohamad Hafiz; Mohamed, Juliza; Zainal Azim, Zainal Azhar (UUM Press, 2023)
The rise in the cost of living is the leading cause of stress. Therefore, it is essential to investigate the impact of financial burdens on health. However, to date, limited studies have examined the relationship between financial burden and cardiovascular disease risk factors, the leading cause of death in the world, including Malaysia. Hence, this study examined the determinants of coronary heart disease (CHD). The study administered a questionnaire on CHD patients in Selangor, the most populated State in Malaysia. A total of 300 valid responses were obtained and analysed using multiple regression analysis. The results showed that accommodation cost, salary, smoking habit, age, residential area, marital status and education level are associated with CHD. Nevertheless, the study did not find support for the relationship between education expenses and employment status on CHD. Based on the results, this study recommends that the government and housing developers increase housing affordability, particularly for low- and middle-income earners. Besides, everyone should enjoy a high quality of life regardless of job type or salary. Health awareness, particularly CHD risk, should be promoted regularly in all communication media to target a wider group, particularly the elderly.